2020
DOI: 10.3390/metabo10110473
|View full text |Cite
|
Sign up to set email alerts
|

Sphingolipid Profiling Reveals Different Extent of Ceramide Accumulation in Bovine Retroperitoneal and Subcutaneous Adipose Tissues

Abstract: Sphingolipids are bioactive lipids that can modulate insulin sensitivity, cellular differentiation, and apoptosis in a tissue-specific manner. However, their comparative profiles in bovine retroperitoneal (RPAT) and subcutaneous adipose tissue (SCAT) are currently unknown. We aimed to characterize the sphingolipid profiles using a targeted lipidomics approach and to assess whether potentially related sphingolipid pathways are different between SCAT and RPAT. Holstein bulls (n = 6) were slaughtered, and SCAT an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Sphingolipids of the de novo synthesis pathway, such as sphinganine, dihydroceramide, and Cer, were more concentrated in RPAT than in SCAT [90]. Sphingolipids of the salvage pathway and the sphingomyelinase pathway, such as SPH, S1P, ceramide-1-phosphate, glycosphingolipid, and SM, were more concentrated in SCAT [90]. This unique distribution of sphingolipids may contribute to differences in insulin sensitivity, inflammation, and oxidative stress between RPAT and SCAT in cows with SCK.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Sphingolipids of the de novo synthesis pathway, such as sphinganine, dihydroceramide, and Cer, were more concentrated in RPAT than in SCAT [90]. Sphingolipids of the salvage pathway and the sphingomyelinase pathway, such as SPH, S1P, ceramide-1-phosphate, glycosphingolipid, and SM, were more concentrated in SCAT [90]. This unique distribution of sphingolipids may contribute to differences in insulin sensitivity, inflammation, and oxidative stress between RPAT and SCAT in cows with SCK.…”
Section: Discussionmentioning
confidence: 90%
“…Leung et al [90] observed variations in sphingolipid compositions between bovine RPAT and SCAT, notably finding higher ceramide levels in RPAT than in SCAT. Sphingolipids of the de novo synthesis pathway, such as sphinganine, dihydroceramide, and Cer, were more concentrated in RPAT than in SCAT [90]. Sphingolipids of the salvage pathway and the sphingomyelinase pathway, such as SPH, S1P, ceramide-1-phosphate, glycosphingolipid, and SM, were more concentrated in SCAT [90].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sphingolipid metabolome was quantified by a targeted liquid chromatography-mass spectrometry (LC-MS) based metabolomics assay in the liver, muscle, and subcutaneous adipose tissue samples. This analysis was carried out at the UVic Node of The Metabolomics Innovation Centre (TMIC; Genome BC Proteomics Centre, The University of Victoria, Victoria, BC, Canada) following the previously published workflow ( Leung et al, 2020 ). The 77 compounds targeted herein belonged to the following sphingolipid classes: 3-keto-sphinganine (3-KSpha), sphinganines (Spha), sphinganine-1-phosphates (Spha-P), dihydroceramides (dhCer), dihydroceramide-1-phosphates (dhCer-P), ceramides (Cer), ceramide-1-phosphates (Cer-P), galactosyl-ceramides (GalCer), glucosyl-ceramides (GlcCer), lactosyl-ceramides (LacCer), sphingomyelins (SM), dihydrosphingomyelins (dhSM), and sphingosines (Spho).…”
Section: Methodsmentioning
confidence: 99%
“…Equine plasma samples, collected at 0 and 120 minutes, relative to glucose administration, were used for sphingolipid analysis at The Metabolomic Innovation Centre (TMIC UVic Node at The University of Victoria, Genome BC Proteomics Centre, Victoria, British Colombia, Canada), as reported previously. 24 Briefly, 50 μL of sample were mixed with 0.95 mL of methanol‐chloroform (5:2), including 0.1 mg/mL of butylated hydroxytoluene as antioxidant. The sample mixtures then were vortexed for 30 seconds, sonicated for 5 minutes in an ice bath, and centrifuged for 20 minutes at 21 000 g at 10°C to precipitate proteins.…”
Section: Methodsmentioning
confidence: 99%